Computational prediction and experimental validation of revolute joint clearance wear in the low-velocity planar mechanism. (15th February 2017) - Lai, Xiongming; He, Huang; Lai, Qinfang; Wang, Cheng; Yang, Jianhong; Zhang, Yong; Fang, Huaiying; Liao, Shuirong
Abstract: Within the multibody dynamics framework, the paper proposed an efficient procedure to calculate revolute joint wear of planar mechanism with low velocity. Firstly, based on the wear test data, a method to calculate the wear coefficient that corresponds to the actual working condition of the mechanism is proposed. Then, an efficient iterative prediction method for joint clearance wear evolving in the multibody dynamic system in is proposed based on the Archard's wear model. Meanwhile, the wear tests of the typical mechanism have verified the method proposed in this paper. The research shows that when the increments of the wear depth of revolute joints are not big, the method can provide high prediction accuracy; however, as the predicted wear depth increases, the prediction error increases as well. Highlights: A efficient wear prediction method for revolute joint is proposed. The wear coefficient is computed based on the partial wear test data. The wear tests was used to verified the proposed prediction method. The method agrees well with reality when the wear increment is not large.